The Impact of the Case Management Model at MedZou Community Health Clinic - Lesko, David; Day, Jesse; Honig, Rachel; Howenstine, Debra; Lindbloom, Erik (Journal of Student-Run Clinics, 2017)
MedZou Community Health Clinic is the University of Missouri’s student-run clinic (SRC) that serves the uninsured of central Missouri. While successful, MedZou has faced barriers to delivering continuity and coordination of care, spurring the creation of the Case Management Model (CMM) in 2013. This innovative model consists of medical students serving as case managers, case management directors, and MedZou clinic directors, supported by physician advisors. At its foundation, a case manager is paired with a patient who has a chronic, complex medical history along with multifactorial psychosocial issues. The case manager assesses each patient’s health needs, helps them navigate medical resources, and coordinates their medical care with the help of a physician advisor. This report describes two cases that demonstrate how the CMM has led to improvements in coordination and continuity of health care. Case 1 involves a patient with severe psoriasis who obtained mandatory lab testing before starting Humira® (adalimumab) and received Humira free of charge. Case 2 involves a patient who received timely treatment for a myocardial infarction, as well as help with Family and Medical Leave Act paperwork, medication coverage, and accessing social services post-hospitalization. In each case, the CMM led to greatly improved health outcomes and quality of life for patients and provided case managers with valuable educational experiences. We believe that this simple model can be easily implemented at other SRCs and we urge its adoption to better serve communities abroad.